LES SAXONS DE TRANSYLVANIE ET LEURS ÉGLISES FORTIFIÉES: UN RICHE PATRIMOINE CULTUREL DE LA ROUMANIE - DANIEL IOSIF (Revue Roumaine de Géographie)
A great German civilization is living for about 800 years in Transylvania. They improved the indigenous life and technology. They built the largest area in the world with fortified churches, more than 200 in a relatively small area (Hârtibaciu’s hills). With a huge cultural potential, the villages which are inhabited by Saxons are in a visible economic decline. Almost every village being here dispose of a fortified church, witness to Transylvanian history and culture. Most of them are now abandoned, which is directly linked to the exodus of Transylvanian Saxons. Seven of them are now UNESCO heritage sites and can be visited, a true museum of German art.